Arts : Le Havre 2006 : biennale d'art contemporain = biennial of contemporary art - Blouin, Patrice; Boisvert, Anne-Marie; Gosselin, Claude; Morren, Linda; Le Havre (Le Havre : Arts Le Havre, 2006)
Antille, Emmanuelle ; Atelier van Lieshout ; Bilodeau, Jacques ; Birchler, Alexander ; Boetti, Alighiero ; Bonk, Ecke ; Claxton, Dana ; Colomer, Jordi ; Cormier, Claude ; Debord, Guy ; van Elk, Ger ; Goulet, Michel ; Heward, John ; Hill, Gary ; Höller, Carsten ; Hubbard, Teresa ; Just, Jesper ; Larsson, Annika ; Minkoff, Gérald ; Morellet, François ; Morelli, François ; Robbe, Hervé ; Ruscha, Edward ; Snow, Michael ; Thomkins, André ; Tunga ; Verjux, Michel
Publication à l'occasion de l'exposition 'Arts: Le Havre 2006: biennale d'art contemporain = biennial of contemporary art' à Le Havre, 01.06.2006-25.06.2006
boek